Analisis Produk Simpan Pinjam di Koperasi Pegawai Dinas Ketahanan Pangan dan Peternakan Provinsi Jawa Barat Bandung - Reliyani Atje; Indirani; Wawan Lulus Setiawan (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
Economic development during a pandemic like today has experienced a decline. Many trade and business sectors have been forced out of business in the face of this pandemic. One of the causes is the declining purchasing power of the community, and also the existence of government regulations that require working from home (Work From Home.) The result of the research in this report is that we know about the procedures that apply in the employee cooperative of the West Java Province Food Security and Livestock Service Office. And we can know at a glance about the amount of interest and the distribution of the remaining proceeds from the business in the Employee Cooperative of the Food Security and Livestock Service Office of West Java Province. The conclusion obtained in making this report is that the employee cooperative of the West Java provincial food security and livestock service has five requirements, three provisions that must be obeyed and has six stages of the procedure as well as an interest rate of 1.5%.